Development of an on-line and intelligent energy saving scheme for a commercial building - Majid, Md. Shah (Universiti Teknologi Malaysia, 2006)
In Malaysia, during the past two decade, demand for commercial sector grew rapidly, increasing at an average rate of 7.5 percent in the 1980s and 7.7 percent in 1990s, surpassing the GDP growth of 5.9 percent and 7 percent over the corresponding period. At present, the commercial sector has utilized 19% of the total energy usage for the all sectors. In the context of commercial building, the air conditioning is the main energy usage which consumes 70% of the electrical energy used while the remaining 30% used for lighting and other loads. This research project is to design and develop an Air Conditioning control system and external light infiltration control system. Fuzzy will be used to determine the definite value of control signal in order to identify and to monitor the energy usage in the efficient way. The development of this proposed energy intelligent control scheme would be able to control the energy consumption of the commercial building using on-line monitoring.